Cosmic-ray energy reconstruction using machine learning techniques - Alvarado, A.; Capistrán, T.; Torres, I.; Sacahuí, J. R.; Alfaro, R.; Albert, A.; Alvarez, C.; Andrés, A.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; et al. (Proceedings of Science, 2024)
HAWC is a ground-based observatory consisting of 300 water Cherenkov detectors, which observes the extensive air showers induced by cosmic rays from some TeV to a few PeV and, in particular, gamma rays from 300 GeV to more than 100 TeV. One of the crucial features required for a detector of extensive air showers is the estimation of the primary energy of the events to study the spectra of cosmic and gamma rays. For HAWC there are currently two gamma-ray energy estimators: one relies on a ground density parameter, while the other utilizes an artificial neural network. For the cosmic ray energy estimation, there is only one estimator based on maximum likelihood procedures and measurements of the lateral charge distribution of the events. It is worthwhile to update the cosmic-ray energy estimator due to recent improvements of the extensive air shower offline-reconstruction techniques in HAWC. Therefore, we implemented an artificial neural network to reconstruct the primary energy of hadronic events trained with several observables that characterize the air showers. We trained several models and evaluated their performance against the existing cosmic ray energy estimator. In this work, we present the features and performance of these models.
CRIS-Team Scopus Importer:2025-02-04